Bridging the Divide between Theory and Applied Research: New Ecological Measures as Pathways to Ecological Balance - Leslie, Carrie M.; Burns, Thomas; Hekmatpour, Peyman (European Journal of Applied Sciences, 2022)
In studying environmental problems, it is beneficial when theoretical and applied approaches work in synthesis, bridging gaps towards potential solutions. This paper calls for the utilization of new ecological measures (NEMs) in scientific research. We offer discussion and examples. Applied research advances with a shared discourse of measures that adequately bridges theoretical investigation and applied studies, allowing for transdisciplinary collaboration. A shared discourse of new ecological measures is crucial to outline how the scope, extent and severity of ecological problems can be operationalized as new measures, adding clarity and in some cases pointing toward prudent policy implications and action.